Tashmim al-Mauqi’ al-Ta’limi Muassasan ‘ala at Tahlil at-Taqabuli li Tanmiyati Maharati al-Kitabah li Thullab al-Fashl al-Dirasi al-Khamis bi Qismi Ta’lim al-Lughah al-‘Arabiyyah fil al-Jami’ah al Islamiyyah al-Hukumiyyah Bone - Rahmad Hidayat Lubis; Zulkifli Hayad; Maulana Ashari (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2021)
This study aims to develop, validate, and evaluate the effectiveness of a contrastive analysis–based learning website for improving the Arabic writing (Inshā’) skills of fifth-semester students in the Arabic Language Education Study Program at the State Islamic Institute (IAIN) Bone. The study was motivated by the fact that many students are graduates of non-Islamic boarding schools or institutions with limited exposure to intensive Arabic language practice, making it difficult for them to achieve the expected writing proficiency within the available instructional time. To address this issue, the researcher designed a web-based learning resource that presents Inshā’ materials based on contrastive analysis, enabling students to better understand the differences between Arabic and their first language. The research employed a Research and Development (R&D) approach combined with a True Experimental Design using a non-equivalent control group. Data were collected through interviews, questionnaires, writing tests, and documentation. Qualitative data were analyzed using the Miles and Huberman model, while quantitative data were analyzed using the independent-samples t-test with the assistance of SPSS. The results indicate that the developed learning website possesses clear instructional characteristics based on the Dick and Carey instructional design model. The website is specifically intended for beginner-level learners and enables students to compose simple, coherent, and systematic Arabic essays by constructing well-organized sentences on familiar topics. Expert validation confirmed the feasibility of the website, with validation scores of 95.8% and 85.5%, while small-group and field trials also demonstrated highly satisfactory results. Students’ average achievement improved from a pre-test score of 62.3 to a post-test score of 72.2. Furthermore, the effectiveness test produced a significance value of 0.000, which is lower than the 0.05 significance level, indicating that the learning website significantly enhances students’ Arabic writing skills. These findings suggest that the developed website is both valid and effective and can serve as an alternative or supplementary learning resource for Inshā’ instruction, particularly for learners with similar educational backgrounds and language proficiency levels.